Bibliometric research on urban thermal comfort related to urban planning legislation and computer simulation: a time frame from 2020 to 2025 - Ribeiro, Fabiana Martins; Soares, Joadellio Chagas (Scientific Journal ANAP, 2025)
Objective – The general objective of this work was to carry out a bibliometric survey of scientific publications found in the Scopus database between 2020 and 2025 on urban thermal comfort together with the themes of urban legislation and computer simulation. Methodology – A bibliographical survey was carried out together with a literature review on the topics involved. Originality/Relevance – The work presents a topic that is becoming increasingly relevant today due to the increase in temperature in urban environments and the need to study the subject more and find solutions to alleviate the thermal discomfort felt by people. Results – The research showed that there are few studies on urban thermal comfort related to urban legislation, with little theoretical basis on the subject. As for urban thermal comfort in relation to computer simulation, the number of publications increases every year, showing that this is a promising area. Theoretical/Methodological Contributions – The study shows the feasibility of studying more about urban thermal comfort, especially in relation to urban legislation, as there was little research found, but it is also important to continue academic research on urban thermal confrontation analysis through computer simulations. Social and Environmental Contributions – The study is important because it allows us to study ways of mitigating the harmful effects caused by rising temperatures in the urban environment, which are consequences of climate change.